1993
DOI: 10.1177/089124393007002007
|View full text |Cite
|
Sign up to set email alerts
|

Changes in U.S. Men's Attitudes Toward the Family Provider Role, 1972-1989

Abstract: This article examines changes in men's attitudes toward the family provider role using data from the National Opinion Research Center, General Social Surveys for 1972 through 1989. Men's attitudes have become more egalitarian over this period; however, men approve more of sharing provider-role enactment than of sharing provider-role responsibility. Cohort succession was a more important source of change than change within cohorts. Differences among men in attitudes toward the provider role were associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 8 publications
4
100
1
Order By: Relevance
“…For men, age, education, income level, marital status, and their spouses' employment status are all strong predictors. Older, less educated, married men with full-time homemaker wives in the USA are less egalitarian in their views than younger, unmarried, more educated, high-status men with full-time employed wives (Wilkie 1993).…”
Section: Gender-role Beliefsmentioning
confidence: 99%
“…For men, age, education, income level, marital status, and their spouses' employment status are all strong predictors. Older, less educated, married men with full-time homemaker wives in the USA are less egalitarian in their views than younger, unmarried, more educated, high-status men with full-time employed wives (Wilkie 1993).…”
Section: Gender-role Beliefsmentioning
confidence: 99%
“…Consistent with these assumptions, the small existing body of survey-based evidence has found that, as a group, Latinas/os are less egalitarian in their attitudes toward gender when compared to non-Hispanic whites or African Americans (Harris and Firestone 1998;Strong et al 1994;Wilkie 1993). Although some observers have also reported significant attitudinal differences toward gender exhibited by Latina/o national origin groups (e.g., (Montoya 1996)), others have found few meaningful differences of this sort (Harris and Firestone 1998).…”
Section: Latina/o Gender Ideology: Integrating Current Research Withmentioning
confidence: 74%
“…However, some researchers have argued against the emphasis on acculturation since this focus caricatures and exaggerates the degree of male dominance in Latina/o culture, wherein micro-level gender relations are highly contested (e.g., (Baca Zinn 1980;Segura 1992)). In addition to acculturation, studies have shown that structural factors like education, employment, and economic resources are associated with greater gender egalitarianism among Latinas/os and other groups (Phinney and Flores 2002;Vasquez-Nuttall et al 1987;Wilkie 1993).…”
Section: Latina/o Gender Ideology: Integrating Current Research Withmentioning
confidence: 99%
“…Examining differences across cohorts rather than years, modeling the varying effects of education on gender egalitarianism rather than just the level of gender egalitarianism, and testing nonlinear predictions of an integrative diffusion theory all help extend the literature in new directions. Making comparisons across cohorts builds on other studies (Brewster and Padovic 2000;Brooks and Bolzendahl 2004;Ciabattari 2001;Schnittker, Freese, and Powell 2003;Wilkie 1993) but also more fully exploits the potential for change to occur across groups that are born and socialized in different historical periods. Modeling interactions between cohort and education captures both the diffusion of gender egalitarianism and the importance of cohort sources of social change.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have analyzed consecutive cross-sectional surveys in the United States (Bolzendahl and Myers 2004;Brewster and Padavic 2000;Carter, Corra, and Carter 2009;Mason and Lu 1988;Rindfuss, Brewster, and Kavee 1996;Spitze and Huber 1980), and several examine the influence of cohort on attitudes (Brooks and Bolzendahl 2004;Schnittker, Freese, and Powell 2003;Wilkie 1993). Several others have examined attitudinal differences across nations (Scott, Alwin, and Braun 1996;Treas and Widmer 2000).…”
Section: Hypothesesmentioning
confidence: 99%